Identification of the Related Substances in Ampicillin Capsule by Rapid Resolution Liquid Chromatography Coupled with Electrospray Ionization Tandem Mass Spectrometry - Lei Zhang; Xian Long Cheng; Yang Liu; Miao Liang; Honghuan Dong; Beiran Lv; Wenning Yang; Zhiqiang Luo; Mingmin Tang (Journal of Analytical Methods in Chemistry)
Rapid Resolution Liquid Chromatography coupled with Electrospray Ionization Tandem Mass Spectrometry (RRLC-ESI-MSn) was used to separate and identify related substances in ampicillin capsule. The fragmentation behaviors of related substances were used to identify their chemical structures. Finally, a total of 13 related substances in ampicillin capsule were identified, including four identified components for the first time and three groups of isomers on the basis of the exact mass, fragmentation behaviors, retention time, and chemical structures in the literature. This study avoided time-consuming and complex chemosynthesis of related substances of ampicillin and the results could be useful for the quality control of ampicillin capsule to guarantee its safety in clinic. In the meantime, it provided a good example for the rapid identification of chemical structures of related substances of drugs.